2021
DOI: 10.1177/23094990211002002
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative laxity of the lateral soft tissue is largely negligible in total knee arthroplasty for varus osteoarthritis

Abstract: Purpose: To evaluate the integrity of lateral soft tissue in varus osteoarthritis knee by comparing the mechanical axis under varus stress during navigation-assisted total knee arthroplasty before and after compensating for a bone defect with the implant. Methods: Sixty-six knees that underwent total knee arthroplasty were investigated. The mechanical axis of the operated knee was evaluated under manual varus stress immediately after knee exposure and after navigation-assisted implantation. The correlation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Other studies have indicated that PCL resection increases the lateral flexion gap more than the medial flexion gap 15,22 . Some researchers have reported that varus knee deformity results in a progressive laxity of the lateral soft tissues 23,24 . Our results showed that the greater the varus deformity, the greater the ratio of the lateral to medial gaps, which indicates that varus deformity is correlated with an imbalance of the medial and lateral gaps.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Other studies have indicated that PCL resection increases the lateral flexion gap more than the medial flexion gap 15,22 . Some researchers have reported that varus knee deformity results in a progressive laxity of the lateral soft tissues 23,24 . Our results showed that the greater the varus deformity, the greater the ratio of the lateral to medial gaps, which indicates that varus deformity is correlated with an imbalance of the medial and lateral gaps.…”
Section: Discussionsupporting
confidence: 58%
“…15,22 Some researchers have reported that varus knee deformity results in a progressive laxity of the lateral soft tissues. 23,24 Our results showed that the greater the varus deformity, the greater the ratio of the lateral to medial gaps, which indicates that varus deformity is correlated with an imbalance of the medial and lateral gaps. Even after the osteophytes were removed and the ACL resected, that is, before PCL resection, a correlation still exists.…”
Section: Flexion and Extension Gapsmentioning
confidence: 62%